Effect of a sigma-1 receptor agonist, cutamesine dihydrochloride (SA4503), on photoreceptor cell death against light-induced damage. (March 2015) - Shimazawa, Masamitsu; Sugitani, Sou; Inoue, Yuki; Tsuruma, Kazuhiro; Hara, Hideaki
Abstract: Cutamesine dihydrochloride is an agonist of sigma-1 receptor, which is a ligand-operated receptor chaperone at the mitochondrion-associated endoplasmic reticulum (ER) membrane. ER stress plays a pivotal role in light irradiation-induced retinal damage. In the present study, we examined whether cutamesine is effective against experimental degenerative retinal damages in vitro and in vivo . The effects of cutamesine against white light-induced retinal photoreceptor damage were evaluated in vitro by measuring cell death. The expression of sigma-1 receptor after the light exposure was examined by immunoblot analysis. The disruption of the mitochondrial membrane potential and caspase-3/7 activation after excessive light exposure were also examined. In addition, retinal damage in mice induced by irradiation to white light was evaluated using histological staining and electroretinography. Cutamesine reduced the cell death rate induced by light exposure, and the protective effect was prevented by N-[2-(3, 4-dichlorophenyl)ethyl]-N-methyl-2-(dimethylamino)ethylamine (BD-1047) dihydrobromide, a sigma-1 receptor antagonist. Sigma-1 receptor expression was decreased by light exposure, and cutamesine suppressed the decreased expression of sigma-1 receptor protein. Cutamesine also reduced the mitochondrial damage and reduced the elevated level of caspase 3/7 activity; this effect was attenuated by BD-1047. In in vivo studies, cutamesine suppressed the light-induced retinal dysfunction and thinning of the outer nuclear layer in the mouse retina. These findings indicate that cutamesine protects against retinal cell death in vitro and in vivo by the agonistic effect of sigma-1 receptor. Therefore, sigma-1 receptor may have a potential as a therapeutic target in retinal diseases mediated by photoreceptor degeneration. Highlights: Cutamesine, a sigma-1 receptor agonist, reduced the 661W cell death induced by light exposure. Cutamesine also reduced the mitochondrial damage and reduced the elevated level of caspase 3/7 activity. Cutamesine suppressed the light-induced retinal dysfunction and thinning of the outer nuclear layer in the mouse retina. Sigma-1 receptor may have a potential as a therapeutic target in retinal diseases mediated by photoreceptor degeneration.